PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP MINAT BERKUNJUNG WISATAWAN DOMESTIK KE MUSEUM SURABAYA - Syahrul Hidayat; I Ketut Suwena; N.G.A.S. Dewi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2021)
Surabaya City currently lacks of potential natural tourism, Surabaya needs new alternative tourism to increase tourists to visit Surabaya by making museum tours become a tourist attraction. One of the factors that influencing tourists to visit are the promotion factor and service quality. This research was conducted to find out the influence of promotion and service quality towards interest to visit to museum Surabaya. The promotion aims to provide & attract tourists to visit. The quality of service is needed so that tourists feel comfortable to visit the museum and desire to revisit museum. The accidental sampling technique used by distributing questionnaires to 100 local tourists who visiting the museum . Multiple linear regression was used to measure the effect of independent variables on the dependent variable using SPSS version 24.0. The results of this research showed that the promotion variable (X1) does not partially had a positive and significant effect on tourit interest (Y) with t-count 1,629 < t-table 1,984. Service quality variable (X2) partially had a positive and significant effect with t-count 6,907 > t-table 1,984.Promotion variable (X1),and service quality variable (X2) simultaneously have a positive and significant effect with F-count 35,561 > F-table 3.939. Based on the results of multiple linear regression test, obtained the regression equation is Y = 13,849 + 0,200 X1 + 0,366 X2 + e with the correlation coefficient of 0.650 and the determination coefficient of 0.411 (41,1%).